LETM1 Knockdown Promotes Autophagy and Apoptosis Through AMP-Activated Protein Kinase Phosphorylation-Mediated Beclin-1/Bcl-2 Complex Dissociation in Hepatocellular Carcinoma - Zhou, Baoyong; Yang, Changhong; Yan, Xiong; Shi, Zhengrong; Xiao, Heng; Wei, Xufu; Jiang, Ning; Wu, Zhongjun (Frontiers in Oncology, 2021)
The leucine zipper/EF hand-containing transmembrane-1 (LETM1) is one of the mitochondrial inner membrane proteins which has been reported to be involved in many primary tumors and could regulate many biological processes. However, the biological role and molecular mechanism of LETM1 in the progression of hepatocellular carcinoma (HCC) remains largely unknown. In this study, we found that LETM1 was highly expressed in HCC tissues and cell lines; and high-expressed LETM1 was associated with a lower overall survival rate of HCC patients. In addition, LETM1 knockdown inhibited the proliferation, and aggravated the apoptosis and autophagy in Huh 7 and QGY-7701 liver cancer cell lines. Mechanically, knockdown of LETM1 dissociated Beclin-1/Bcl-2 complex through AMPK phosphorylation and Bcl-2 phosphorylation. These results demonstrated that LETM1 was involved in the development of HCC which could be a novel therapeutic target against HCC.